PENGEMBANGAN E-MODUL INTERAKTIF MODERASI BERAGAMA DALAM KONTEKS KONSELING BAGI MAHASISWA BIMBINGAN DAN KONSELING ISLAM - Aulia Rachma Fajria (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2026)
Islamic Religious College (PTKI) bears a strategic responsibility in shaping students who are not only academically excellent, but also moderate in character, inclusive, and capable of becoming agents of peace within a pluralistic society. Students of Islamic Guidance and Counseling (BKI) uniquely require the internalization of religious moderation (wasathiyyah) values not only as muslims, but also as prospective counselors who will engage directly with clients from diverse religious and cultural backgrounds. However, no teaching materials have specifically integrated religious moderation values into BKI professional competencies. This study aims to develop an interactive e-module that integrates religious moderation values with counseling competencies for BKI students. Employing the Research and Development (R&D) method with the ADDIE model, the e-module was developed and validated by material and media experts, then trialed with 74 students. Content expert validation yielded a score of 4.08 (feasible), while media expert validation achieved 4.25 (very feasible). Student trials demonstrated strong practicality outcomes, with an overall mean rating of 4.74 (very practical), comprising subscores of 4.67 for design and accessibility, 4.72 for content and instructional methods, and 4.83 for perceived usefulness. These findings confirm that an Islamic values-based religious moderation e-module that bridges wasathiyyah principles with counseling practice is both highly needed and well received by students, and serves as a replicable model for integrating religious moderation values into counselor education within Islamic higher education institutions.